AAV-mediated gene delivery attenuates neuroinflammation in feline Sandhoff disease. (6th January 2017) - Bradbury, Allison M.; Peterson, Tiffany A.; Gross, Amanda L.; Wells, Stephen Z.; McCurdy, Victoria J.; Wolfe, Karen G.; Dennis, John C.; Brunson, Brandon L.; Gray-Edwards, Heather; Randle, Ashley N.; Johnson, Aime K.; Morrison, Edward E.; et al.
Highlights: Neuroinflammation is a prominent pathological feature of feline Sandhoff disease. A robust infiltration and activation of microglia were evident in CNS of SD cats. MHCII and MIP-1α were up-regulated in the brain of SD cats. Intracranial AAV gene therapy attenuated inflammation, normalizing MHCII and MIP-1α. Abstract: Sandhoff disease (SD) is a lysosomal storage disorder characterized by the absence of hydrolytic enzyme β-N-acetylhexosaminidase (Hex), which results in storage of GM2 ganglioside in neurons and unremitting neurodegeneration. Neuron loss initially affects fine motor skills, but rapidly progresses to loss of all body faculties, a vegetative state, and death by five years of age in humans. A well-established feline model of SD allows characterization of the disease in a large animal model and provides a means to test the safety and efficacy of therapeutic interventions before initiating clinical trials. In this study, we demonstrate a robust central nervous system (CNS) inflammatory response in feline SD, primarily marked by expansion and activation of the microglial cell population. Quantification of major histocompatibility complex II (MHC-II) labeling revealed significant up-regulation throughout the CNS with areas rich in white matter most severely affected. Expression of the leukocyte chemokine macrophage inflammatory protein-1 alpha (MIP-1α) was also up-regulated in the brain. SD cats were treated with intracranial delivery of adeno-associated viral (AAV) vectors expressing feline Hex, with a study endpoint 16 weeks post treatment. AAV-mediated gene delivery repressed the expansion and activation of microglia and normalized MHC-II and MIP-1α levels. These data reiterate the profound inflammatory response in SD and show that neuroinflammation is abrogated after AAV-mediated restoration of enzymatic activity.